Challenging issues of average consensus algorithms in wireless sensor networks. (1st June 2016) - Khosravi, Adel; Kavian, Yousef S.
Abstract : This study tackles common challenges of the average consensus algorithms in real‐world distributed wireless networks. The drawbacks of asynchronous transmissions, topology changes and communication delays on the distributed decision making of the network members to terminate a consensus algorithm are mainly studied. Two distributed stopping policies are proposed that help the network members to gradually stop message transmissions when they reach an acceptable accuracy of the final consensus value. Simulation results show that the proposed algorithms help previous consensus algorithms to decrease total packet transmissions in a random topology network. Simulation results also confirm that the proposed can perform in the presence of delayed members and non‐ideal transmissions.